Dream big dreams : photographs from Barack Obama's inspiring and historic presidency - Souza, Pete (Little, Brown and Company, 2017)
Compiles over seventy-five full-color photographs from Barack Obama's historic presidency, accompanied by behind-the-scenes anecdotes, documenting Obama at work, with his family, greeting guests, and on his travels.